The Tao of the West : Western transformations of Taoist thought - Clarke, J. J. (John James), 1937- (Routledge, 2000)
In this book J.J Clarke shows us how Taoist texts, ideas and practices have been assimilated within a whole range of Western ideas and agendas. A fascinating introduction to Taoism and the history of the West's encounter with it.